THE ANALYSIS OF WIRELINE FORMATION TESTER DATA TO OBTAIN RESERVOIR PERMEABILITY - PRAMUDIBYO (NIM: 22215019), BAGUS
Data permeability of a reservoir can be obtained by several methods, such as: core analysis, well log data, Drill Stem Test (DST), Wireline Formation Tester (WFT) or so-called mini-DST. Both the core and DST methods require considerable operating costs until they finally get permeability data. Such large costs result in the limitation of the use of core and DST methods in all reservoir zones present in a well. Another method for obtaining permeability data is mini-DST. Mini-DST is a well test method like DST, but the operating costs of mini-DST are much smaller, and the duration of tests from mini-DST is much shorter. Mini-DST does not use DST, but uses Wireline Formation Tester (WFT) with dual packer. By looking at build up pressure data during the data acqusition on WFT, build up pressure analysis can be done using pressure transient analysis (PTA) method in Ecrin software. If the permeability can be obtained by conventional WFT method using pressure transient analysis (PTA) method, the cost incurred to obtain the permeability data becomes smaller and the time required is also shorter than WFT which is generally used to perform mini-DST, ussualy by using dual packer. In the result of WFT data analysis, from WFT data can be obtained some permeability which are derived from some method. Those are permeability that derived from WFT mobility and permeability derived from PTA result. Compared with the permeability data that derived from well logs, the permeability data from the PTA results have a higher level of consistency and conformity than the permeability data of WFT mobility. Referring to the conformity of permeability results from PTA data of WFT data to permeability of well logs, conventional WFT can be an alternative to obtain permeability data in reservoir zones around the borehole with the most limited cost compared to other methods.